A1_11 The Mexican Wave - Harrison, Joseph Oliver; Carr, Natasha; McCulloch, Ariella; Whitaker, Joshua (Physics Special Topics, 2022)
In this paper a Mexican Wave is compared to and assumed to be similar to a wave on a string. The maximum energy able to be transferred along the 'Mexican wave' is calculated to be 1300 W which is multiplied out to your average section of crowd in a stadium in total generating up to 35 KW. This energy is compared to how much money could be saved for the stadium per hour, of 11.9 p,  from the power used of typical devices in a stadium.